PERKAWINAN EKSOGAMI PADA MASYARAKAT SUKU “ANAK DALAM” DI NAGARI BONJOL DAN BANAI KABUPATEN DHARMASRAYA SUMATERA BARAT - Nola Putriyah P; Makmur Syarif; Salma Salma (Jurnal AL-AHKAM, 2020)
Basically, the Suku Anak Dalam marriage, abbreviated as SAD, adopts an endogamy system, where the SAD community emphasizes that the marriage is conducted by fellow SAD. However, in the end the system experienced a shift to an exogamy, so marriages between SAD and outsiders took place in Nagari Bonjol and Banai. The purpose of this study was to determine the reasons for exogamy marriages in the SAD community and to determine the resilience of ex-family marriages of SAD communities in Nagari Bonjol and Banai.This research is a field research. Data collection techniques through observation, interviews, and documentation. To analyze data, the authors use data reduction, data display, and drawing conclusions or verification. The results of this study stated that: First, the reason for allowing exogamy marriages in the SAD community was due to the acculturation between SAD and the community which had implications for the dynamics of life and the SAD perspective. This makes SAD accept new things outside the customary provisions that have been practiced. Second, a marriage based on the word love alone is a fragile marriage. Therefore, each pair must have a strong religious foundation so that all forms of problems can be faced.